The impact of content familiarity on reading comprehension among male and female students - Mohd Nazri, Latiff Azmi; Hamzah Barakat, Najadat (2019)
The current study investigated the impacts of content familiarity on the comprehension performance of male and female Saudi students. The study adopted the quantitative method and tested thirty-two male and female university students through two gender-neutral texts, one familiar and the other one unfamiliar. The outcomes revealed that content familiarity had meaningful influences on the students' comprehension performance. The study also showed a significant difference between male and female participants in terms of text familiarity with the familiar text. The case is quite similar to the unfamiliar text. The overall result shows that female students outperformed male counterparts in this comprehension test. Such results should be taken into consideration by the curriculum designers